Implementing BIM (Building Information Modeling) in public projects: a case study of the Muniz Sodré Penitentiary. - Carvalho, Rafaela Rodrigues; Carmo, Cristiano Saad Travassos do; Melo, Érica Tavares de (Brazilian Journal of Production Engineering, 2026)
The purpose of this study is to analyze the implementation of the BIM methodology for asset management in the Brazilian public sector, using as a case study the renovation of the electrical system of a correctional facility located in the state of Rio de Janeiro. To this end, the proposed methodology includes the survey of the existing structure and the diagnosis of obsolescence problems, the development of the new electrical project in a BIM platform, and a questionnaire to assess the results and challenges of the implementation. As results, quantitative and qualitative improvements were observed in the management of the built asset, such as increased productivity and greater accuracy in cost and schedule planning, as indicated in the research with the project team. The challenges identified are related to the need for co,ntinuous training, the shortage of technological resources, and the difficulty in organizing data among teams. In conclusion, the study found that the BIM methodology provides greater efficiency, transparency, and cost savings in the maintenance of public buildings; however, it faces barriers that require a gradual process of institutional maturity to effectively integrate the methodology into asset management.
Keywords: Public asset management; penitentiary; Bim methodology